Red Light Triggered Fluorogenic Reaction with Picomolar Sensitivity Toward Nucleic Acids - Zozulia, Oleksii; Bachmann, Tobias; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
We have previously reported on a red light triggered, singlet oxygen-mediated fluorogenic reaction that is templated in a highly sequence specific fashion by nucleic acids (S. Dutta, A. Fulop, A. Mokhir, Bioconjgate Chem.2013, 24 (9), 1533-1542). Up to the present date, it has remained a single templated reaction responsive to nontoxic >650 nm light. However, it is operative only in the presence of relatively high (>2 nM) concentrations of templates that dramatically limit its applicability in nucleic acid detection. In the current work, we established that an inefficient intermolecular electron transfer involved in reduction of the 1,4-endoperoxide intermediate, formed in the rate-limiting reaction step, is responsible for inhibition of the reaction at low reagent concentrations. We suggested the solution of the problem which includes a combination of a cleavable (9-alkoxyanthracene) moiety with a two-electron donating fragment in one molecule. This approach enables the efficient intramolecular electron transfer to the endoperoxide intermediate in the critical reaction step. Due to the intramolecular character of the latter process, it is practically independent of concentration of the reagents. The reaction based on the improved cleavable moiety was found to be >200-fold more sensitive than the previously reported one. It is fast, sequence specific, and compatible with live cells. Accounting for short reactions times (<30 min), nontoxic trigger (red light), excellent sensitivity, and sequence specificity, this is presently the best reported photochemical templated reaction compatible with live cells.
CRIS-Team Scopus Importer:2019-08-09